Bacillus subtilis YlxR, Which Is Involved in Glucose-Responsive Metabolic Changes, Regulates Expression of tsaD for Protein Quality Control of Pyruvate Dehydrogenase - Ogura, Mitsuo; Sato, Tsutomu; Abe, Kimihiro (Frontiers in Microbiology, 2019)
Glucose is the most favorable carbon source for many bacteria, which have several glucose-responsive gene networks. Recently, we found that in Bacillus subtilis glucose induces the expression of the extracellular sigma factor genes sigX and sigM through the acetylation of CshA (RNA helicase), which associates with RNA polymerase. We performed a transposon mutagenesis screen for mutants with no glucose induction (GI) of sigX-lacZ. While screening for such mutants, we recently found that the GI of sigX/M involves YlxR, a nucleoid-associated protein (NAP) that regulates nearly 400 genes, including metabolic genes. It has been shown that acetylated CshA positively regulates expression of ylxR-containing operon. Here, we report additional mutations in yqfO or tsaD required for the GI of sigX. YqfO contains a universally conserved domain with unknown function. YqfO and YlxR were found to regulate expression of the tsaEBD-containing operon. Mutational analysis using lacZ fusions revealed the adenine-rich cis-element for YlxR. TsaD is a component of the TsaEBD enzyme required for the synthesis of threonylcarbamoyl adenosine (t6A). The t6A modification of tRNA is universal across the three domains of life. Western blot analysis showed that the tsaD mutation in the presence of glucose reduced levels of soluble PdhA, PdhB, and PdhD, which are subunits of the pyruvate dehydrogenase complex (PDHc). This resulted in severely defective PDHc function and thus reduced concentrations of cellular acetyl-CoA, a reaction product of PDHc and plausible source for CshA acetylation. Thus, we discuss a suggested glucose-responsive system (GRS) involving self-reinforcing CshA acetylation. This self-reinforcing pathway may contribute to the maintenance of the acetyl-CoA pool for protein acetylation.